2012
DOI: 10.1007/s11745-012-3695-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐induced Vesicular Dynamics of Membranes Containing Cholesterol Derivatives

Abstract: Membrane structural organization is an intrinsic property of a cell membrane. Any changes in lipid composition, and/or any stimuli that affect molecular packing induce structural re-organization. It membrane dynamics provide a means by which changes in structure organization can be determined, upon a change in the membrane internal or external environment. Here, we report on the effect of thermo-stress on membranes containing cholesterol liquid crystal (LC) compounds cholesterol benzoate (BENZO) and oxidized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…EC causes strong packing of lipid molecules and reduces the radii of vesicles and cells. Research will continue on the investigation of properties of membrane containing EC to observe shape transformations under stresses such as osmotic [30], heat [8,9] and so far, to reveal molecular interaction of EC with lipids molecules. Notably, we have to confirm the EC presence in yeast cells, whether it is in the membranes or at other places in the yeast cells.…”
Section: Role Of Ec In Membranesmentioning
confidence: 99%
See 3 more Smart Citations
“…EC causes strong packing of lipid molecules and reduces the radii of vesicles and cells. Research will continue on the investigation of properties of membrane containing EC to observe shape transformations under stresses such as osmotic [30], heat [8,9] and so far, to reveal molecular interaction of EC with lipids molecules. Notably, we have to confirm the EC presence in yeast cells, whether it is in the membranes or at other places in the yeast cells.…”
Section: Role Of Ec In Membranesmentioning
confidence: 99%
“…Although we did not find any reports that testify that yeast has DOPC, an article reported that yeast has both oleic acids and phosphatidylcholine, which are components of DOPC [15]. During previous studies, we have researched the interaction of biological molecules, such as capsaicin [6], oxidized cholesterol [8,9,16], local anesthetics [10,11] proteins [16], polyphenols [17], between membranes lipids. In these studies, there were some approaches, mainly using lipid vesicles.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This study explains the functions of flavor molecules using giant lipid membrane vesicles (liposomes). Previous studies have analyzed the interaction between liposomes and biomolecules such as capsaicin, oxidized cholesterol, local anesthetics, , proteins, and polyphenols, . Moreover, dynamic shape changes are induced by several stimulations such as differences in protein aggregation level, , different polyphenol structures, strength of stimulation on the surfactant, and photo-oxidation of lipids. ,, …”
Section: Introductionmentioning
confidence: 99%